Role of AI in Business Management - Bimalendu Pendy (ITScience (Information Technology and Science), 2023)
The article discusses the increasing applications of AI in business management. In sales and marketing, AI-powered tools can help businesses understand customer needs, create personalized marketing campaigns, and improve customer engagement. AI is also revolutionizing supply chain management, improving efficiency, and agility by analyzing real-time data. Customer service is also transforming through AI-powered chatbots that handle routine queries, allowing human agents to focus on more complex issues. In financial analysis, AI provides accurate and timely insights into financial performance, risk management, and investment opportunities. The article also highlights the benefits of AI, including increased efficiency and productivity, improved accuracy and precision, and better customer experience. It also addresses some challenges of AI in business management, such as data quality and availability, skills and expertise, cost, ethics and bias, and integration with existing systems. Finally, it discusses the future potential of AI in business management, such as predictive analytics, personalized marketing, chatbots, and process automation.